Comparison of phenolic profiles and antioxidant potentials of the leaves and seeds of Thai holy and sweet basils. (9th May 2015) - Shen, Yixiao; Prinyawiwatkul, Witoon; Lotrakul, Pongtharin; Xu, Zhimin
Summary Eight phenolics rosmarinic, caftaric, caffeic, chicoric, p‐hydroxybenzoic, p‐coumaric, protocatechuic acid and rutin were identified in Thai holy/sweet basil leaves or seeds. The overall phenolics in THBL were two, three and twenty times higher than that in TSBL, THBS and TSBS, respectively. Oppositely, the TP content of TSBL was one and a half times higher than THBL which was followed by THBS and TSBS. The order of scavenging DPPH free radical activity from high to low was THBL, TSBL, THBS and TSBS and consistent with their overall phenolics. In a cholesterol oxidation model, THBL exhibited higher antioxidant activity with lower level of 7‐ketocholesterol (2.67 ± 0.31 μg/mL) than TSBL (4.49 ± 0.32), THBS (7.78 ± 1.25) or TSBS (13.10 ± 0.61). The results demonstrated that Thai holy basil has higher antioxidant capability than sweet basil and could be used as an effective bioactive ingredient to provide health‐promoting function in food.